Basic physics learning process in electrical engineering vocational education program using ispring presenter interactive powerpoints to improve student understanding - Irwanto Irwanto (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
The Department of Vocational Education in Electrical Engineering (JPVTE) is one of the departments based in the Faculty of FKIP UNTIRTA. The physics course at JPVTE is a fundamental concept that must be understood by the first half of students Because students' understanding of physics is still lacking, especially in the idea of mechanics. The research objectives are (1) to Facilitate lecturers in the learning process in the classroom and (2) to improve student understanding in understanding the concepts of mechanics in physics learning. The research method used was descriptive qualitative. The techniques of data collection were observation, tests, and interviews. The analysis technique used is to Determine the percentage of conceptual understanding with a percentage description. The Obtained results are (1) Using the Interactive PowerPoint Point Presenter is very easy for physics lecturers to explain and provide basic concepts of understanding mechanics in interacting with students. (2) Interactive Powerpoint iSpring Presenter can improve students' knowledge in understanding the concept of mechanics included in the high category Because The learning is interactive and fun.